Transglutaminase crosslinked sodium caseinate/starch/tri calcium phosphate based flexible sponge grafts - ŞENGÖR, MUSTAFA (My University, 2022)
In this study, sodium caseinate/starch/ tri-calcium phosphate (TCP) base scaffolds were fabricated and cross -linked with microbial transglutaminase. A Maillard reaction was carried out to stabilize the blend of sodium caseinate (8% w/w) and starch (8% w/w) solutions. The dynamics of enzymatic cross-linking activity were assessed with different TCP concentrations. Freeze-dry method was used to extract water from the gel system to acquire a porous, spongy structure. Apart from many other enzymes, microbial transglutaminase has the capa-bility to be active even below freezing temperatures. Keeping at-50 degrees C for 12 h, enzymes were still active to complete the post-crosslinking process. 0.5% TCP case resulted in 690 kPa ultimate tensile strength at dried state. Cell activity and characterization tests were elucidated and observed that those scaffolds can have very prom-ising applications in bone tissue engineering.
Keywords: Fizik; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Natural Sciences; Engineering and Technology; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); FİZİK, UYGULAMALI; Temel Bilimler (SCI); MATERIALS SCIENCE, MULTIDISCIPLINARY; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); PHYSICS, APPLIED; PHYSICS; Natural Sciences (SCI); İstatistiksel ve Doğrusal Olmayan Fizik; Metaller ve Alaşımlar; Malzeme Kimyası; Genel Malzeme Bilimi; Fizik Bilimleri; Statistical and Nonlinear Physics; Metals and Alloys; Materials Chemistry; General Materials Science; Physical Sciences; Polymeric composites; Biomaterials; Biomimetic